Organoid-Based Models for Traumatic Brain Injury: Challenges, Innovations, and Future Perspectives - Gautam, Megha; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Traumatic brain injury (TBI) is a major health concern impacting millions of individuals across the globe. Understanding how TBI damages the brain and finding better treatments are urgent needs. Traditional laboratory models, such as cell cultures and animal studies, often cannot fully represent the complex nature of human brain injuries. Recently, organoid-based models have become exciting new tools in brain research. These models are three-dimensional clusters of brain cells grown from human stem cells, which closely mimic the structure and function of the human brain. Because they come from human cells and grow in three dimensions, brain organoids provide a more accurate and detailed way to study how the brain develops and responds to injury compared with older methods. Brain organoids reproduce several essential characteristics of the developing human brain, making them highly valuable for scientific research. They allow scientists to explore the detailed processes involved in TBI and test new treatment approaches in a controlled laboratory setting. This flexibility and closeness to human biology make organoids a promising platform for advancing TBI research. In this review, we discuss the latest progress in using brain organoids to model TBI. We look at how well these models mimic the injury processes seen in real brain trauma and highlight both the challenges and future possibilities for improving and applying organoid-based models. Overall, organoid technology represents a significant step forward in understanding TBI and developing effective therapies.
Keywords: 3D cell cultures; brain organoids; injury models; mechanical injury; traumatic brain injury (TBI)